Mutation Analysis of the BRCA1 and BRCA2 Genes in the Belgian Patient Population and Identification of a Belgian Founder Mutation BRCA1 IVS5+3A>G. Issue 1 (17th June 2013) - Claes, Kathleen; Machackova, Eva; De Vos, Michel; Poppe, Bruce; De Paepe, Anne; Messiaen, Ludwine
Abstract : Since the identification of the BRCA1 and BRCA2 genes, several hundred different germline mutations in both genes have been reported. Recurrent mutations are rare and mainly due to founder effects. As the mutational spectrum of the BRCA1 and BRCA2 genes in the Belgian patient population is largely unknown, we initiated mutation analysis for the complete coding sequence of both genes in Belgian families with multiple breast and/or ovarian cancer patients and in "sporadic" patients with early onset disease. We completed the analysis in 49 families and in 19 "sporadic" female patients with early onset breast and/or ovarian cancer. In 15 families we identified a mutation (12 mutations in BRCA1 and 3 mutations in BRCA2). In 5 apparently unrelated families the same splice site mutation was identified (BRCA1 IVS5+3A>G). Haplotype analysis revealed a common haplotype immediately flanking the mutation in all families suggesting that disease alleles are identical by descent. In none of the 19 sporadic patients was a mutation found.